Estrategias metodológicas e-learning en el proceso de enseñanza y aprendizaje de la asignatura de lengua y literatura con los estudiantes del séptimo grado paralelo “B” de la Unidad Educativa “Adolfo Valarezo” año lectivo 2021-2022. - Arias Ortega., José David (2022)
The present research is focused on the e-learning methodological strategies and the teaching-learning process, whose problematic is based on assimilating how the new types of tactics affect the development of students within the subject of Language and Literature, especially being framed as general objective which is to analyze the incidence of the e- learning methodological strategies in the teaching and learning process of the subject of Language and Literature of the students from the seventh grade, classroom B of "Adolfo Valarezo" school. Taking that into consideration, the approach of this research work is qualitative-quantitative (mixed), since it allows objectivity to the aim of the study, it also allows the implementation of deductive and inductive processes. Therefore, the collection of quantitative data, which is explained with interpretations or meanings of the researchers, it will be possible to describe the phenomenon as it is currently presented. During the process, the scientific, inductive/deductive, descriptive, analytical, scientific, synthetic and statistical methods were applied, as well as techniques such as surveys, which were initially used in the research work to know the feasibility and convenience of the work to be done and to be able to identify the positive and negative factors of the present research work, additionally, in order to know the origins of the deficiencies or strengths of the work group. As a conclusion, it should be mentioned that among the most significant results the types of e-learning methodological strategies that contribute to the teaching process by the teacher and student learning are: academic forums, academic chat, academic wikis, portfolios and mind maps. Key words: Strategies, Methodology, E-learning, Teaching, Learning.